Can a Green School Building Teach? A Pre- and Post-Occupancy Evaluation of a Teaching Green School Building. Issue 10 (December 2020) - Cole, Laura B.; Hamilton, Erin M.
Amid increasing interests in social metrics within green buildings, this work focuses on buildings designed to enhance environmental education, here called "Teaching Green Buildings" (TGBs). This study examines one school building at three points in time before and after the move into a new construction TGB. Middle school students here and at a local, comparison Non-Green School ( N = 264) took a survey measuring outcomes of green building knowledge (GBK) and environmentally responsible behaviors (ERBs). Regression results showed that GBK is significantly higher for students in the Green School compared with the Non-Green School, but is not increasing over time for students at the Green School. No differences were detected in ERBs across schools or time, and it was found that school practices, more than the green building itself, were pivotal in student choices to conduct ERBs at school.